Pengaruh Economic Value Added (EVA), Market Value Added (MVA) Dan Financial Value Added (FVA) Terhadap Return Saham (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021) - Diah Wahyu Lestari; Abdul Hadi Sirat; Hartaty Hadady (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to determine the effect of Economic Value Added (EVA), Market Value Added (MVA) and Financial Value Added (FVA) on stock returns in manufacturing companies for the 2016-2021 period. The population of this study in all manufacturing companies listed on the indonesia stock exchange for the 2016-2021 period. The type of research used in this research is quantitative research. The sampling technique using the purposive sampling method obtained a sample of 10 manufacturing companies with a total observation during the 2016-2021 period, namely 60. The test tool used is multiple linear regression analysis using SPSS 25 as a statistical test tool. The results showed that EVA and MVA had a positive and significant effect on stock returns, while FVA had no significant effect on stock returns. And testing simultaneously the variables EVA, MVA and FVA have a positive and significant effect on stock returns.